An engineered oncolytic virus expressing PD-L1 inhibitors activates tumor neoantigen-specific T cell responses - Guan Wang (Nature Portfolio, 2020)
Oncolytic viruses can activate tumor neoantigen-specific T cell responses. However, PD-L1 upregulation on tumor cells and immune cells leads to tumor resistance to this immunotherapy approach. Here, the authors develop an oncolytic virus which expresses both a PD-L1 inhibitor and GM-CSF which allows an improved tumor neoantigen-specific T cell response in preclinical models.